2012
DOI: 10.1111/j.1530-0277.2012.01871.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Possible Period 2 Gene Mediation of the Effects of Alcohol Exposure During the Postnatal Period on Genes Associated with Maintaining Metabolic Signaling in the Mouse Hypothalamus

Abstract: Background Animals exposed to alcohol during the developmental period develop circadian disturbances and metabolic problems that often persist during their adult period. In order to study whether alcohol and the circadian clock interact to alter metabolic signaling in the hypothalamus, we determined whether postnatal alcohol feeding in mice permanently alters metabolic sensing in the hypothalamus. Furthermore, we evaluated whether the effect of circadian disruption via Period2 (Per2) gene mutation prevents alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In fact, there is strong and convincing evidence suggesting that alcohol has a profound interaction with circadian rhythms (Agapito, Barreira, Logan, & Sarkar, 2013; Brager, Ruby, Prosser, & Glass, 2011; Chen, Kuhn, Advis, & Sarkar, 2006; Frank et al, 2013; Lindsay, Glass, Amicarelli, & Prosser, 2014; Logan, Williams, & McClung, 2014; Partonen, 2012; Perreau-Lenz & Spanagel, 2008; Prosser, Mangrum, & Glass, 2008; Rosenwasser, 2010; Ruby, Prosser, & Glass, 2006; Seggio, Logan, & Rosenwasser, 2007; Spanagel, Rosenwasser, Schumann, & Sarkar, 2005). We suggest that alcohol may have minimal impact on the circadian regulation of sleep and a more predominant effect on the homeostatic regulation of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is strong and convincing evidence suggesting that alcohol has a profound interaction with circadian rhythms (Agapito, Barreira, Logan, & Sarkar, 2013; Brager, Ruby, Prosser, & Glass, 2011; Chen, Kuhn, Advis, & Sarkar, 2006; Frank et al, 2013; Lindsay, Glass, Amicarelli, & Prosser, 2014; Logan, Williams, & McClung, 2014; Partonen, 2012; Perreau-Lenz & Spanagel, 2008; Prosser, Mangrum, & Glass, 2008; Rosenwasser, 2010; Ruby, Prosser, & Glass, 2006; Seggio, Logan, & Rosenwasser, 2007; Spanagel, Rosenwasser, Schumann, & Sarkar, 2005). We suggest that alcohol may have minimal impact on the circadian regulation of sleep and a more predominant effect on the homeostatic regulation of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the liver, alcohol exposure in a high-fat diet did result in increased nuclear accumulation of Sirt1 (Nascimento, Ip, Luvizotto, Seitz, & Wang, 2013), and Sirt1 mRNA transcripts were also found to be induced in the dorsal hippocampus in peri-pubertal mice following chronic alcohol exposure (Prins et al, 2014). However, in the alcoholic liver model, deacetylase activity was actually reduced (Nascimento et al, 2013) and others have shown that early postnatal alcohol exposure to alcohol results in prolonged suppression of Sirt1 mRNA transcripts in the hypothalamus (Agapito, Barreira, Logan, & Sarkar, 2013). These data collectively show that epigenetic regulators like Sirt1 may be subject to multiple regulatory controls aside from miRNAs and that ethanol regulation of miRNAs may not yield predictable outcomes, even for known direct miRNA targets.…”
Section: Mirnas As Mediators Of Ethanol Effects In Developing and Adumentioning
confidence: 90%
“…During the preceding decade, a new family of genes has emerged as a major player in the addiction field: the so-called clock genes (Agapito, Barreira, Logan, & Sarkar, 2013; Agapito, Mian, Boyadjieva, & Sarkar, 2010; Falcón & McClung, 2009; Logan, Williams, & McClung, 2014; McCarthy, Fernandes, Kranzler, Covault, & Welsh, 2013; McClung, 2007; Perreau-Lenz & Spanagel, 2008; Rosenwasser, 2010). Clock genes, such as Period genes ( Per1-Per3 ), Cryptochrome genes ( Cry 1–2 ), Circadian Locomotor Cycle Kaput - ( Clock ), Brain and Muscle ARNT-like protein 1 ( Arntl1 ), Neuronal PAS domain protein 2 (NPAS2 ), or D-box-binding protein (Dbp) genes are molecular components of the circadian clockwork.…”
Section: Clock Genes – New Key Players In Aud and Sudsmentioning
confidence: 99%